Effect of Supplying Rosemary (Rosmarinus officinalis L.) and Garlic (Allium sativum L.) Essential Oils to Feedlot Lambs on in vitro Ruminal Fermentation - Cavalheiro Junior, Elias Rodrigues; Serafim, Camila Cano; Rodrigues, Erica Regina; Guerra, Geisi Loures; do Carmo, João Pedro Monteiro; dos Santos, Tayna Fernandes; Simonelli, Sandra Maria; Poveda Parra, Angela Rocio; Mizubuti, Ivone Yurika; Prado Calixto, Odimári Pricila (Frontiers in Animal Science, 2021)
The aim of this trial was to evaluate the ruminal degradation kinetics of carbohydrates in diets with different roughage:concentrate ratios and dosages of garlic and rosemary essential oils, in order to find the most suitable dosage to supply feedlot lambs. Three roughage:concentrate ratios (50:50, 40:60, and 20:80) and six dosages of garlic and rosemary essential oils (0.0, 0.10, 0.25, 1.0, 1.50, and 2.0 g L−1) were tested. Kinetic parameters for carbohydrate breakdown were estimated using a semi-automated in vitro gas production technique. Ruminal degradation parameters were subjected to variance analysis and then regression analysis at a 5% significance level. There was no interaction between the roughage:concentrate ratios and the dosage of rosemary essential oil. The roughage:concentrate ratios in diets with rosemary oil affected the non-fiber carbohydrate degradation rate (Kdnfc), colonization time (L), gas volume and breakdown rate from the degradation of fiber carbohydrates (Vfc and Kdfc, respectively), and final gas volume of both fiber and non-fiber carbohydrates (Vfinal). Rosemary dosages affected Vnfc and Vfc, which presented a quadratic response with a peak at 0.71 g L−1 and a nip at 1.17 g L−1, respectively. Bacterial colonization time was quadratic, reaching a maximum value at 1.18 g L−1. Vfinal showed a decreasing linear trend, such that each gram of rosemary essential oil added to the diet could reduce gas production by 30.312 mL. Therefore, rosemary essential oil has an effect on carbohydrate degradation kinetics. There was no interaction between roughage:concentrate ratios and different garlic oil dosages, except for colonization time. Roughage:concentrate ratios with garlic oil had affected the Vnfc, Kdnfc, and L. Garlic oil dosages affected Vfc and Vfinal in a quadratic manner, with the lowest values of gas production at 1.35 and 1.54 g L−1, respectively. L was affected by the garlic oil dosage and roughage:concentrate ratios in a decreasing linear trend for a 50:50 ratio and quadratic response for a 40:60 ratio, peaking at 0.14 g L−1. Based on these in vitro results, a ruminal content of 1.0 g L−1 is recommended for both rosemary and garlic essential oils.